FORMULA ENTERAL “ BITASOY" BERBASIS TEPUNG UBI JALAR UNGU (IPOMOEA BATATAS L), TEPUNG KETAN HITAM (ORYZA SATIVA. VAR. GLUTINOSA), DAN TEPUNG TEMPE (RHIZOPUS ORYZAE) UNTUK PASIEN DM - Hapsari, Agustina Indri; Isdiany, Nitta; Fauziyah, Roro Nur; Syara, Rani (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2024)
ABSTRACT According to IDF (International Diabetes Federation) data in the 10th edition of the IDF Atlas, it is stated that in Indonesia, the estimated population of adult diabetes aged between 20-79 years is 19,465,100 people, so it is known that the prevalence of diabetes between the ages of 20-79 years is 10 .6% (IDF, 2021). Diabetes mellitus (DM) is a chronic disease characterized by hyperglycemia due to defects in insulin production and action or both (American Diabetes Association, 2013). Nutritional therapy or diet therapy for DM is part of the treatment of a disease or clinical condition that must be taken into account so that its administration does not exceed the ability of the body's organs to carry out metabolic functions. Enteral nutrition is a therapy that provides nutrients in the form of liquid food either orally or using a special tube (feeding tube). Enteral formulas consist of commercial formulas and hospital formulas. The aim of this research is to develop a formula and organoleptic test of the "BITASOY" enteral formula based on purple sweet potato flour (Ipomoea batatas L), black sticky rice flour (Oryza Sativa. var. glutinosa) and tempe flour (Rhizopus oryzae) as a choice of home formula food. pain for DM patients. The research results showed that based on the organoleptic test, F2 was the formula most preferred by the panelists.   Key words: Enteral Formula, Diabetes Mellitus, Purple Sweet Potato Flour, Tempe Flour, Anthocyanins, Flavonoids